2021
DOI: 10.1002/icd.2226
|View full text |Cite
|
Sign up to set email alerts
|

Observed and reported coparenting and toddlers' adaptive functioning

Abstract: This study examined the associations between perceived and observed coparenting and toddlers' adaptive functioning. Seventy‐seven typically developing toddlers aged between 21 and 27 months and their biological parents residing in Ireland participated in the study. Participating families were Caucasian and English speaking. Parents' perceived coparental relationship was assessed via self‐report. In addition, coparenting dynamics were observed during triadic free‐play and structured‐play tasks. Mothers reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…A growing body of research has revealed direct associations between coparenting relationship quality and child outcomes ( Teubert and Pinquart, 2010 ). In particular, when parents do not support each others’ parenting strategies, child adjustment suffers ( Nandy et al, 2021 ). In contrast, when coparenting support is high, children exhibit fewer internalizing and externalizing difficulties ( Farr et al, 2019 ).…”
Section: The Development Of Self-regulationmentioning
confidence: 99%
“…A growing body of research has revealed direct associations between coparenting relationship quality and child outcomes ( Teubert and Pinquart, 2010 ). In particular, when parents do not support each others’ parenting strategies, child adjustment suffers ( Nandy et al, 2021 ). In contrast, when coparenting support is high, children exhibit fewer internalizing and externalizing difficulties ( Farr et al, 2019 ).…”
Section: The Development Of Self-regulationmentioning
confidence: 99%
“…Increased positive coparenting has also been moderately linked to increased academic achievement in school ( Dopkins Stright and Neitzel, 2003 ; Cabrera et al, 2012 ), faster language development, and increased social functioning ( Cheng et al, 2009 ). Negative coparenting has been linked with behavior problems ( LeRoy et al, 2013 ), reduced communication and social skills ( Nandy et al, 2021 ), poor child adjustment and later psychopathology ( Umemura et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%